2010
DOI: 10.1038/sj.bjc.6605507
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of mapatumumab, a fully human agonistic monoclonal antibody that targets and activates the tumour necrosis factor apoptosis-inducing ligand receptor-1 (TRAIL-R1), in patients with refractory colorectal cancer

Abstract: BACKGROUND: Recombinant tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) induces tumour-selective apoptosis in various pre-clinical models by binding its specific receptors expressed on cancer cells. Mapatumumab is a fully human monoclonal antibody that is agonistic to the TRAIL Receptor 1 (TRAIL-R1). METHODS: This phase II multicentre study was designed to evaluate the efficacy and safety of mapatumumab in patients with colorectal cancer (CRC) who had failed to respond to, were intolerant to, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
96
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(97 citation statements)
references
References 40 publications
0
96
0
1
Order By: Relevance
“…However, some tumor cells seem resistant to the killing effect of TRAIL, and resistance could be acquired following therapeutic TRAIL delivery in patients (10). This suggests that TRAIL therapies will be most effective when used in combination with agents which can sensitize tumor cells to TRAIL (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…However, some tumor cells seem resistant to the killing effect of TRAIL, and resistance could be acquired following therapeutic TRAIL delivery in patients (10). This suggests that TRAIL therapies will be most effective when used in combination with agents which can sensitize tumor cells to TRAIL (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Although clinical trials with recombinant TRAIL protein and agonistic antibodies to TRAIL-receptor 2 (TRAIL-R2) have shown that they are safe, only moderate evidence of therapeutic efficacy has been observed [8][9][10][11]. One of the problems, despite frequent high-dose injections, is insufficient bioavailability at the site of tumor growth owing to a short half-life of TRAIL protein in the circulation [12].…”
Section: Introductionmentioning
confidence: 99%
“…This clinical failure has been subsequently attributed to the low in vivo bioactivity of the TRAIL molecules administered, and their rather short terminal plasma half-life (»1 hour). 4,6 Consequently, alternative therapeutic strategies targeting TRAIL death receptors have been developed, such as agonistic monoclonal antibodies directed against either DR4, e.g., mapatumumab, 8,9 or DR5, e.g., conatumumab 10 and lexatumumab. 11 However, Phase 1 and 2 clinical studies revealed ambiguous results (for review see refs.…”
Section: Introductionmentioning
confidence: 99%